2009
DOI: 10.1118/1.3148534
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the feasibility of relative 3D dosimetry in the Radiologic Physics Center Head and Neck IMRT phantom using Presage/optical‐CT

Abstract: This study presents the application of the Presage/optical-CT 3D dosimetry system for relative dosimetry in the Radiologic Physics Center ͑RPC͒ Head and Neck ͑H&N͒ IMRT phantom. Performance of the system was evaluated by comparison with the "gold-standard" RPC credentialing test. A modified Presage cylindrical insert was created that extended the capability of the RPC H&N phantom to 3D dosimetry. The RPC phantom was taken through the entire treatment planning procedure with both the standard RPC insert and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…It has been noted in previous studies that there exists a volume effect where sensitivity and response over time may differ subtly based on the volume of the dosimeter. 7,10 An in depth examination of these volume effects is beyond the scope of this work, but as shown in Fig. 9 and discussed below, linear response over time was confirmed for the large volume cylindrical dosimeters for this study.…”
Section: B2b Relative Temporal Stability In Dosimetersmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been noted in previous studies that there exists a volume effect where sensitivity and response over time may differ subtly based on the volume of the dosimeter. 7,10 An in depth examination of these volume effects is beyond the scope of this work, but as shown in Fig. 9 and discussed below, linear response over time was confirmed for the large volume cylindrical dosimeters for this study.…”
Section: B2b Relative Temporal Stability In Dosimetersmentioning
confidence: 99%
“…As previously published, sensitivity differences have been observed between measurements in small volume optical cuvettes versus larger dosimeters. 7,10 Consequently, calibration curves derived from small volume cuvettes have been found to result in dose discrepancies of 4%-7% when applied to large volume dosimeters. Thus, measured dose distributions were calibrated with corresponding cuvette-based calibrations, then normalized to the central high dose region.…”
Section: D2 Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The scattering and absorption properties of the radiation dosimeter should be comparable to the water. 2 The radiological properties and the formulation have been studies by many writers and it was observed that PRESAGE ® (Heuris Inc., Skillman, NJ) has effective atomic number (7.6) close to water (7.42). 3 PRESAGE ® is a radiochromic three dimensional dose measuring dosimeter which is composed of polyurethane and radiochromic components (Leuco dyes) and halogen containing free radical initiator 4 that have an optical attenuation coefficient that changes linearly with absorbed dose.…”
Section: Introductionmentioning
confidence: 99%